Exploring the challenges of structural peacebuilding in Sub-Saharan Africa : a case study of peacebuilding in post-civil war Somalia 2013 to 2018 - Wielenga, Cori (University of Pretoria, 2019)
Mini Dissertation MA (Diplomatic Studies))--University of Pretoria, 2019.